Transarterial Chemoembolization and Radioembolization across Barcelona Clinic Liver Cancer Stages - Titano, Joseph; Noor, Amir; Kim, Edward (Seminars in Interventional Radiology, 2017)
Transarterial chemoembolization (TACE) is a well-established treatment for hepatocellular carcinoma (HCC). TACE has a clearly delineated role within the Barcelona Clinic Liver Cancer (BCLC) staging framework, and TACE has been shown to bridge patients to transplantation and to downsize patients' tumor burden to meet transplantation criteria. Radioembolization (RE) also has an evolving role in the treatment of HCC. RE has evidence-based applications across the range of BCLC stages ranging from segmentectomy for patients with solitary lesions not amenable to ablation to lobar therapy for patients with multifocal HCC, and to treatment of advanced disease with portal vein thrombosis. This article aims to elucidate the evidence behind these therapies and to provide a rationale for their utilization across the spectrum of BCLC stages in the treatment of HCC.
Keywords: interventional oncology; transarterial chemoembolization; radioembolization